OR05-5THE SURVEY FOR THE MEASURES AGAINST ALCOHOL RELATED PROBLEMS AT MUNICIPAL LEVEL. (September 2014) - Maesato, H.; Tsushita, K.; Higuchi, S.
Abstract : Japan has placed emphasis on tertiary prevention of alcohol-related problems, but not on primary and secondary prevention. However, in 2002, one of the goals of Health Promotion in the 21st century announced by the Ministry of Health, Labour and Welfare was decreasing the number of heavy drinkers. Furthermore, in 2012, the Ministry also started specific health guidance, in which medical insurers are supposed to ask risky drinkers to reduce their alcohol intake by a brief intervention. On the other hand, it is not clear how many municipalities actually take the proposed measures what kind of methods they use, and what the differences among municipalities are. The purpose of our study was to elucidate the measures taken against alcohol-related problems at the municipal level in Japan. Method. This survey subjects were public health nurses in every municipality. The subjects were sent questionnaires, and returned their replies by post. The questionnaire included questions about the population, the number of public health nurses of each municipality, the frequency of intervention on alcohol-related problems, and the method of intervention. Result. We are collecting the responses to the questionnaire, and shall report the results of the questionnaire survey at the meeting.